Transcriptomic profiling revealed important roles of amino acid metabolism in fruiting body formation at different ripening times in Hypsizygus marmoreus - Xiang, Quanju; Arshad, Muhammad; Li, Yakun; Zhang, Huijuan; Gu, Yunfu; Yu, Xiumei; Zhao, Ke; Ma, Menggen; Zhang, Lingzi; He, Maolan; Chen, Qiang (Frontiers in Microbiology, 2023)
Introduction Hypsizygus marmoreus is an industrial mushroom that is widely cultivated in East Asia. Its long postripening stage before fruiting severely limits its industrialized production. Methods Five different mycelial ripening times (30, 50, 70, 90, and 100 d) were chosen and primordia (30P, 50P, 70P, 90P, and 110P) were collected for comparative transcriptomic analyses. The corresponding substrates (30F, 50F, 70F, 90F, and 110F) were used for nutrient content and enzyme activity determination. Results In pairwise comparisons between 110P and other primordia, a total of 1,194, 977, 773, and 697 differentially expressed genes (DEGs) were identified in 30P_110P, 50P_110P, 70P_110P, and 90P_110P, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes Genomes (KEGG) functional enrichment analyses revealed that the DEGs were mainly associated with amino acid metabolism, and lipid and carbohydrate metabolism pathways. Tyrosine, tryptophan, phenylalanine and histidine metabolism were enriched in all groups. Among the main carbon nutrients, the contents of cellulose and hemicellulose were high, and the lignin content decreased with the extension of the ripening time. Laccase had the highest activity, and acid protease activity decreased with the extension of the ripening time. Discussion The highly enrichment for amino acid metabolic pathways in primordia reveals that these pathways are essential for fruiting body formation in H. marmoreus, and these results will provide a basis for the optimization of its cultivation.